TO STUDY PALLIATION OF SYMPTOMS BY A HYPOFRACTIONATED RADIOTHERAPY SCHEDULE IN ADVANCED INOPERABLE SQUAMOUS CELL CARCINOMAS OF THE ORAL CAVITY - PRIYA, MUNAGAPATI VISHNU; REDDY, BEEREDDY KARTHIK; KRISHNA, KADARLA; SUDHARANI, PONUGOTI; RAMAKRISHNA, MALLADI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to study palliation of symptoms and improvements in quality of life (QoL) in inoperable squamous cell cancers of the oral cavity with a hypofractionated radiotherapy schedule. Methods: It is a prospective and observational study in patients with locally advanced squamous cell cancers of the oral cavity attending the outpatient clinic who have been deemed inoperable after discussion in a multidisciplinary team were considered. The data was tested using Friedman’s test for the significance in QoL. Results: All of the functional scales were found significant in this study with physical functioning, emotional functioning and cognitive functioning (CF) being significant at 1% alpha level while role functioning (RF) and social functioning (SF) are significant at 5% alpha level. RF was assessed based on the capabilities of the patient to finish daily activities. The median score remained at 33 but the interquartile range (IQR) was showing an increasing trend. Both pain and head-and-neck specific pain had significantly reduced over time. Fatigue had shown a constant reduction during radiation and during the first follow-up as well. The increase in nausea, vomiting, and constipation during radiation can be attributed to the use of morphine during radiation for pain control and as an effect of radiation itself. There was weight loss during radiation which improved during subsequent follow-up visits. Conclusions: In patients diagnosed with inoperable oral cavity cancer, hypofractionated radiotherapy delivering 50 Gy in 20 fractions over 4 weeks is a well-tolerated and safe regimen. In our study, statistically significant QoL improvement in global health score, SF, and CF lasting for a minimum of 6 weeks was attained after completion of treatment with this regimen.